2003
DOI: 10.1016/s0009-9236(03)00225-x
|View full text |Cite
|
Sign up to set email alerts
|

Cisapride disposition in neonates and infants: in vivo reflection of cytochrome P450 3A4 ontogeny

Abstract: (1) In neonates and infants, cisapride absorption and metabolism to its primary metabolite, norcisapride, were developmentally dependent; (2) approximately 99% of cisapride CL/F in neonates and young infants was nonrenal in nature; (3) CL/F of cisapride in neonates and infants noted in this study was reduced compared with data from older children and adults, likely as a result of developmental reductions in CYP3A4 activity; (4) as reflected by the correlation between postconceptional age and lambda(z), a rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 36 publications
1
23
1
Order By: Relevance
“…Many studies described the hepatic ontogeny of CYP3A isoforms. CYP3A7, detected in fetal liver, was replaced by increasing protein and activity levels of CYP3A4 after birth (Lacroix et al, 1997;Kearns et al, 2003). In contrast, in our duodenal samples, after birth, CYP3A4 mRNA expression decreased significantly after the first month of life to reach adult levels.…”
Section: Discussioncontrasting
confidence: 61%
“…Many studies described the hepatic ontogeny of CYP3A isoforms. CYP3A7, detected in fetal liver, was replaced by increasing protein and activity levels of CYP3A4 after birth (Lacroix et al, 1997;Kearns et al, 2003). In contrast, in our duodenal samples, after birth, CYP3A4 mRNA expression decreased significantly after the first month of life to reach adult levels.…”
Section: Discussioncontrasting
confidence: 61%
“…It was previously demonstrated that gastric empting rates increase during the first 7 days of life [12]. Correspondingly, time to maximum blood concentrations (T max ) have been observed to decrease during the first few weeks of life for some drugs like cisapride where T max at 42-54 weeks is nearly half-that observed at 28-36 weeks [13]. However, a recent meta-analysis challenges the theory that emptying matures as a function of age, proposing rather that the type of food administered to the child is more impactful [12,14].…”
Section: Peroral Administrationmentioning
confidence: 99%
“…143 7 days after birth have only traces of CYP3A4, 144 whereas at the age of 1 month the enzyme activity constitutes only 30% to 40% of an adult's activity. 145 CYP3A4 activity can be assessed with the erythromycin respiratory test. 101 No polymorphism of the enzyme has been reported so far; nevertheless, sexdependent activity variations were observed (women have CYP3A4 activity 20% to 50% higher than men) regarding erythromycin, methylprednisolone, methadone, tacrolimus, modafinil, diltiazem, nifedipine, triazolam, cyclosporine, and verapamil (Table 12 146,147 ).…”
Section: Gastroesophageal Refluxmentioning
confidence: 99%